Implementasi Metode Pembelajaran Total Phisical Response terhadap Mata Pelajaran Bahasa Inggris Sekolah Dasar - Yulia Sukmiyanti; Suryani Suryani; Mia Audina Musyadad (Jurnal Pendidikan Dirgantara, 2025)
The rare of English in Indonesia in communicating in everyday life one of the reasons students have difficulty in memorizing and understanding English. Because of this, the author made a study that aims ti find out how much influence the Total Physical Response (TPR) learning method hason the learning outcomes of fourth grade elementary school students at SDN Lemah Duhur III. This research uses a quantitative approach with a pretest-posttest experiment. Giving pretest ang posttest question, student interviews and observations during learning took place as a source of data that researchers obtained. A total of 10 fourth grade students who participated in English learning activities in memorizing and understanding Engtlish using the TPR method became research subjects. The research show the results of significant increase between before using the TPR methode and after using TPR method.